The political economy of domestic tax reform in Bangladesh: political settlements, informal institutions and the negotiation of reform - Hassan, Mirza; Prichard, Wilson (Routledge, 2016)
This article was published in The Journal of Development Studies [©1916 Published by Taylor & Francis Online] and the definite version is available at: http://doi.org/10.1080/00220388.2016.1153072 The Article's website is at: http://www.tandfonline.com/doi/abs/10.1080/00220388.2016.1153072